Increasing Revisit Intention Through Interpretation Media Design in Gunung Wayang Agrotourism - Silaningsih, Endang; Magdalena Melani, Maria; Budi Setiawan, Ade; Luthfiany, Delia; Hakim, Luqman; Zidan, Muhamad; Shabila Wenintias, Siti (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
The purpose of this Community Partnership Program is to enhance the visitor experience at Gunung Wayang Agrotourism through the development of interpretation media. Interpretation connects visitors with attractions by providing essential information, particularly when direct communication is not feasible. Gunung Wayang Agrotourism, located in Gunung Endut Village, Sukabumi Regency,offers various facilities such as swimming pools, playgrounds, gazebos, coffee shops, exhibition stages, fruit gardens, traditional culinary experiences, and nature exploration. Despite its diverse attractions, the absence of effective interpretation media negatively affects visitor satisfaction, with approximately 40% of visitors expressing dissatisfaction due to limited informational tools, such as inadequate signage and information boards. The methods employed in this program include participatory and collaborative approaches, involving surveys, interviews, discussions, trials, and evaluations. The outcomes of the program include recommendations for improving interpretation facilities, such as creating a more detailed and visually informative 3D layout map and designing clearer directional signage to provide easy-to-follow guidance for visitors. These enhancements aim to improve visitors' understanding and enjoyment of the site, fostering a more engaging experience. With these improvements, it is anticipated that visitor satisfaction will increase, encouraging repeat visits and supporting the sustainable development of Gunung Wayang Agrotourism.